Enhancing Algerian ESP Learners' Lexical Proficiency through Summative Assessment: the Case of Second Year Dental Surgery Students - Assia BOUZID & Amine BELMEKKI (Akofena)
Abstract: The present research explores the significance of summative assessment in promoting dental surgery students’ lexical proficiency. this study is quasi-experimental research that combines both quantitative and qualitative analyses, to evaluate the impact of summative assessment on Algerian second-year dental surgery students’ lexical proficiency. Two main tools of data collection were opted for to retrieve the necessary data. A survey questionnaire in addition to a pre and post vocabulary tests were employed to measure vocabulary retention and application. Findings show that the employed summative assessment strategies significantly improve students' lexical proficiency and facilitates their use and usage of the retained vocabulary in both academic and clinical contexts. This research emphasizes the importance of summative assessments’ strategies to optimize vocabulary learning outcomes.